2010
DOI: 10.1111/j.1440-172x.2010.01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after Caesarean risk decision‐making: Australian findings on the mothers' perspective

Abstract: The purpose of this paper is to explore, from the mothers' perspective, the decision-making experience with regard to subsequent birth choice for women who had previously delivered by Caesarean section. A qualitative methodological approach was taken to the exploration of mothers' knowledge of the risks of vaginal birth after Caesarean (VBAC) or elective Caesarean following a prior birth by Caesarean section. This paper presents the insights provided by the four women who chose VBAC. The health professionals' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…The results show that four studies are from Australia [13,18,19,29], three from UK [2,20,30], and one from US [31]. The women's experiences were requested concerning different aspects of the following phenomena: experiences of decision-making - whether to give birth vaginally or with CS during the subsequent birth [2,13,20], experiences of the influence of health professionals on decision-making [30], reason for trying a vaginal birth after a previous CS [18,20,31], experiences when choosing VBAC [18,19,29], experiences during the subsequent birth giving birth vaginally [18,20,31], and experiences with CS during the subsequent birth [13,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that four studies are from Australia [13,18,19,29], three from UK [2,20,30], and one from US [31]. The women's experiences were requested concerning different aspects of the following phenomena: experiences of decision-making - whether to give birth vaginally or with CS during the subsequent birth [2,13,20], experiences of the influence of health professionals on decision-making [30], reason for trying a vaginal birth after a previous CS [18,20,31], experiences when choosing VBAC [18,19,29], experiences during the subsequent birth giving birth vaginally [18,20,31], and experiences with CS during the subsequent birth [13,30].…”
Section: Resultsmentioning
confidence: 99%
“…The perspective of pregnant women regarding birth risks in a subsequent pregnancy following prior CS are not well understood [13]. There is a great deal of research based on quantitative approaches on VBAC but very few qualitative studies about women's experiences [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true should the preference of the medical team be at odds with her preference (Cherniak and Fisher, 2008). Bourgeault et al (2010) commented that in part, women are more likely to request a repeat caesarean than a primary caesarean because of the powerful influence of their clinicians, a finding also seen by Goodall et al (2009) andMcGrath et al (2010). Based on this prior research, women in our sample who have had a previous caesarean and are currently considering a vaginal birth may well change their birth preference as the pregnancy progresses.…”
Section: Limitationsmentioning
confidence: 93%
“…3,4 We have demonstrated that an evidence-based INFORM video presentation for prelabour rupture of membranes at term is a valuable tool in improving patient satisfaction and involvement in decision-making and is easily incorporated into clinical practice. Future research priorities include validation of the INFORM methodology, as well as measuring its effectiveness to support women considering their next birth after caesarean section, water birth, analgesic options in labour or induction of labour.…”
Section: Discussionmentioning
confidence: 99%
“…However, the quality and quantity of information given to women about options for care can be variable and may be subject to individual clinician bias. 2 There is evidence that the information exchange is sometimes undermined by the provision of inconsistent evidence 3 the bias of some clinicians towards intervention, 4 clinician's tendency to over-emphasise the potential for harm when women choose not to accept intervention, and women's tendency to comply with clinician's suggestions.…”
Section: Introductionmentioning
confidence: 99%